Simulation and Modelling. The Spray Behaviour of Ammonia-Biodiesel Fuel Blends and Injector Characteristics in Micro-Gas Turbine - Mohd Shariff, Syahmi Wafiy; Sulaiman, Syabillah; Azizul, Muhammad Asri (Progress in Engineering Application and Technology, 2022)
Ammonia is one of carbon-free fuel that are considered to be alternative fuels. Liquid ammonia is blended with biodiesel fuel in order to further reduce emissions and to achieve more stable combustion. The premix injector design is specially designed to suite the application of the combustion system which is the micro-gas turbine. The aim of this research is to study and analyses the spray performance of the ammonia-CPO fuel blend on the premix injector nozzle. The method for this research is by using CFD simulation approach where ANSYS software was used to perform the simulation. The solver for the simulation is the SST turbulence model as it is one of the most suitable turbulence models for internal flow simulation. Diesel fuel was used first for baseline comparison to flow through the injector. Then three percentage blends of ammonia-CPO biodiesel were used next to observe and analyses its spray behaviour. The three percentages of ammonia-CPO biodiesel blends were 2% ammonia with 98% CPO, 4% ammonia with 96% CPO, and 6% ammonia with 94% CPO. From the simulation results, diesel fuel had the lower velocity flow and turbulence kinetic energy compared to the ammonia-CPO biodiesel fuel blends. The 6% ammonia with 94% CPO percentage blends had the highest maximum velocity than other percentage blends. The study shows that the ammonia element in the ammonia-CPO biodiesel fuel influenced the spray performance in premix injector.